The Relationship between Students' Paraphrasing Ability, Reading Comprehension, and Vocabulary Mastery - Adek Enggar Rinjani; Ririn Ovilia (Journal of English Language Teaching, 2023)
To complete academic papers, students are expected to write it based on ideas obtained in reading various sources. While doing so, paraphrasing can be done and it is considered as a higher academic skill than quoting. However, in practice, most of students still find it difficult to paraphrase and their ability in paraphrasing is still low. Several studies investigated the problems experienced by students when paraphrasing and it showed that vocabulary and text comprehension are the most frequent problems in this regard. This correlational study aims to identify the relationship and to measure the contribution of students’ reading comprehension and vocabulary mastery to their paraphrasing ability. The population of this study is eight classes of second-year English Language Education students enrolled in the Academic Writing course in English Language Education study program at Universitas Negeri Padang. By using cluster random sampling, two classes were chosen as the sample of this study. The instruments used were in the form of tests which are reading comprehension test, vocabulary level test, and paraphrasing test. This study used quantitative research methods with multivariate and bivariate correlation analysis technique. The findings show that students’ reading comprehension and vocabulary mastery, both separately and simultaneously, are correlated positively with students’ paraphrasing ability. The results also indicate that reading comprehension contributed 10.1% to paraphrasing ability and vocabulary mastery contributed 22.5%.